Effects of auricular stimulation on weight- and obesity-related parameters: a systematic review and meta-analysis of randomized controlled clinical trials - Hua, Kevin; Usichenko, Taras; Cummings, Mike; Bernatik, Miriam; Willich, Stefan N.; Brinkhaus, Benno; Dietzel, Joanna (Frontiers in Neuroscience, 2024)
Background Over the last three decades, the number of randomized controlled trials (RCTs) using stimulation of auricular vagal sensory nerves by means of electrical stimulation, auricular acupuncture, or acupressure to support weight loss has increased markedly. This systematic review focuses on the effects of auricular stimulation (AS) on anthropometric parameters and obesity-related blood chemistry. Methods and analysis The following databases were searched until November 2021: MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), ISI Web of Science, and Scopus Database. Data collection and analysis were conducted by two reviewers independently. Quality and risk assessment of included studies was performed using the risk of bias tool of the Cochrane Handbook, and the meta-analysis of the effect of the most frequently assessed biomarkers was conducted using the statistical software RevMan. Results The full texts of 1,274 studies were screened; 22 contained data on obesity-related outcomes, and 15 trials with 1,333 patients were included in the meta-analysis. The overall quality of the included trials was moderate. AS significantly reduced body mass index (BMI) (mean difference (MD) = −0.38 BMI points, 95% CI (−0.55 to −0.22), p < 0.0001), weight (MD = −0.66 kg, 95% CI (−1.12 to −0.20), p = 0.005), waist circumference (MD = −1.44 cm, 95% CI (−2.69 to −0.20), p = 0.02), leptin, insulin, and HOMA insulin resistance compared to controls. No significant reduction was found in body fat, hip circumference, ratio of waist/hip circumference, cholesterol, LDL, triglycerides, adiponectin, ghrelin, and glucose levels. The AS was safe throughout the trials, with only minor adverse reactions. Conclusion The study results suggest that a reduction of weight and BMI can be achieved by AS in obese patients; however, the size of the effect does not appear to be of clinical relevance. The effects might be underestimated due to active sham trials. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021231885.